Performans Reproduksi Sapi Perah di Peternakan Sapi Fries Holland (FH) Novisiat Claretian Benlutu - Hildegardis Lake; Theresia I. Purwantiningsih (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2020)
Reproductive management is very important as a support for the achievement of high milk production. The better reproductive success of a dairy cow will have an impact on the better production of milk produced. This research has been carried out at the Fries Holland (FH) cattle farm, Claretian Benlutu Novitiate in March 2019, with the aim of obtaining an overview of the reproductive performance of dairy cows at the Claretian Benlutu Novisiat dairy farm. The research method used was a survey method and direct observation to the farm business location, and sampling techniques using total sampling. The research variables observed included: a). Age at first child (Age at first calving), b). Free time (Days open), and c). The calving interval (calving interval). The results showed that the reproductive performance of dairy cows at Fries Holland (FH) Novetian Claretian Benlutu monastery did not show good performance because it exceeded the optimal time for these six variables where the average age of first calving was 37.67 ± 1.53 months, the blank period (Days Open) 170 ± 62.45 days, the interval of calving (Calving Interval) is 450 ± 79.37 days, pubertas is 22,33 ±1,53 months, post partum estrus (PPE) 73,63 ± 10,97 days and post patum mating (PPM) 76,67 ± 11,93 days. In order to improve reproductive performance and better production performance, it is targeted for processors to improve maintenance management according to the management of dairy cattle maintenance.